Perencanaan Jalur Ventilasi dan Sistem Jaringan Ventilasi Udara Pada Tunnel Mainshaft Auxiliaryshaft Tambang Bawah Tanah PT. Allied Indo Coal Jaya Sawah Lunto - Noval Satria; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. There are two kinds of underground mining systems which are natural ventilation systems and mechanical ventilation systems. The air quantity at the front of J6 and J7 does not meet the permitted standards in the Minister of Energy and Mineral Resources RI No. 1827 K / 30 / MEM / 2018. The air quantity at the front of J6 is 1,136m3 / second the air needed is 7,233 m3 / second and the amount of air in front of J7 is 1,528 m3 / second while the amount needed is at 7,167 m3 / second. At Front Junction 6, the available air demand is 1,136 m3 / sec while the air required is 7,233m3 / sec. A blower of 8.3 Kw ≈ 10.5 Kw is needed, and at the front of Junction 7 the available air demand is 1,528 m3 / s, the air needed is 7,167 m3 / s for the air demand when mining activities are needed, the blower power is 8.9 Kw ≈ 10,5 Kw. New air circulation modeling design using Kazemaru software.Keywords: Vetilation Lines, Ventilation Network Sistem,Underground Mining, Air Quality and Air Quantity